2021
DOI: 10.1186/s13063-020-04990-z
|View full text |Cite
|
Sign up to set email alerts
|

Identifying student opinion leaders to lead e-cigarette interventions: protocol for a randomized controlled pragmatic trial

Abstract: Background After the US Surgeon General declared youth electronic cigarette (e-cigarette) use an epidemic in 2018, the number of youth e-cigarette users continued to surge, growing from 3.8 million in 2018 to over 5 million 2019. Youth who use e-cigarettes are at a substantially higher risk of transitioning to traditional cigarettes, becoming regular cigarette smokers, and increasing their risk of developing tobacco-related cancer. A majority of youth are misinformed about e-cig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…For example, prevention programs may benefit from incorporating peer-oriented strategies such as fostering resistance to peer pressure among nonusers or using peer-lead approaches to reduce e-cigarette use among users. In a recent publication, Chu and colleagues showed the feasibility of such a program: peer-lead approaches were well accepted among teachers and students [ 31 , 32 ]. Compared to an expert-led approach, peer-led approaches were more engaging; despite being statistically non-significant partially due to the limited sample size, point estimates suggested that peer-led approaches may be more effective than an expert-lead approach [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, prevention programs may benefit from incorporating peer-oriented strategies such as fostering resistance to peer pressure among nonusers or using peer-lead approaches to reduce e-cigarette use among users. In a recent publication, Chu and colleagues showed the feasibility of such a program: peer-lead approaches were well accepted among teachers and students [ 31 , 32 ]. Compared to an expert-led approach, peer-led approaches were more engaging; despite being statistically non-significant partially due to the limited sample size, point estimates suggested that peer-led approaches may be more effective than an expert-lead approach [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent publication, Chu and colleagues showed the feasibility of such a program: peer-lead approaches were well accepted among teachers and students [ 31 , 32 ]. Compared to an expert-led approach, peer-led approaches were more engaging; despite being statistically non-significant partially due to the limited sample size, point estimates suggested that peer-led approaches may be more effective than an expert-lead approach [ 31 ]. Previous studies on adolescent alcohol use further suggest that peer influence can be a malleable socio-environmental factor for prevention and intervention [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, prevention programs may bene t from incorporating peeroriented strategies such as fostering resistance to peer pressure among nonusers or using peer-lead approaches to reduce e-cigarette use among users. In a recent publication, Chu and colleagues showed the feasibility of such a program: peer-lead approaches were well accepted among teachers and students (35,36). Compared to an expert-led approach, peer-led approaches were more engaging; despite being statistically non-signi cant partially due to the limited sample size, point estimates suggested that peer-led approaches may be more effective than an expert-lead approach (35).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent publication, Chu and colleagues showed the feasibility of such a program: peer-lead approaches were well accepted among teachers and students (35,36). Compared to an expert-led approach, peer-led approaches were more engaging; despite being statistically non-signi cant partially due to the limited sample size, point estimates suggested that peer-led approaches may be more effective than an expert-lead approach (35). Previous studies on adolescent alcohol use further suggest that peer in uence can be a malleable socio-environmental factor for prevention and intervention (Duncan et al).…”
Section: Discussionmentioning
confidence: 99%
“…While there have been studies on preventing vaping among adolescents [ 12 , 13 ], and the effect of vaping misinformation on attitudes toward vapes [ 1 ], and vaping misinformation more broadly [ 10 , 14 , 15 ], there is limited research on interventions to mitigate misinformation about vapes. Thus, we are far from knowing when and how to intervene best.…”
Section: Introductionmentioning
confidence: 99%